Decolonizing Game Literacy - Robinson, Petra A.; Williams, Kamala V.; Stojanović, Maja; Paula, Bruno de (Global Citizenship for Adult Education: Advancing Critical Literacies for Equity and Social Justice, 2022)
In the last decades, digital games have moved from niche to mainstream. As more people play, talk about, and engage with these artifacts, they have become an important part of contemporary cultures, giving rise to game literacy—the set of skills needed to meaningfully engage with video games. While the potentials of game literacy have, to some extent, been already discussed in the literature, we have not adequately discussed the need for a game literacy that problematizes the sociocultural dimensions of gaming, including the hegemonic, exclusionary rationales implicitly disseminated through mainstream gaming. In this chapter, I outline a decolonial model for game literacy, remarking how the reflection about the gaming circuits of production and dissemination should be part of any initiative that aims at dealing with critical and creative competences towards gaming, and how these are crucial for any citizen in contemporary societies.
OCLC: 1288078892
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Décentrer l’histoire du jeu vidéo ? - Derfoufi, Mehdi (De l'autre côté, 2018)
Peut-on envisager une autre histoire du jeu vidéo ?
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Open World Empire: Race, Erotics, and the Global Rise of Video Games - Patterson, Christopher B (New York University Press, 2021)
Seeking ways to understand video games beyond their imperial logics, Patterson turns to erotics to re-invigorate the potential passions and pleasures of play.
OCLC: 1237769915
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Google-Books-ID: Gv5cDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Games Studies India Talk #12: Geoffrey Fernandez - Game Studies India Adda (Game Studies India Adda, 2021)
Counter-Hegemonic Representations of Japanese Cultural Icons in Sekiro Abstract: Through fictional or non-fictional narratives, media representations of the past communicate specific interpretations, which lets users negotiate the past's prospective meanings. Additionally, these cultural constructions of the past are produced and disseminated in the present. Hence, the existing hegemonic power relations influence the depiction and recognition of cultural communities in the construction of the past. Therefore, the approach to framing cultures in pop-culture representations becomes a preponderating factor in how people perceive such cultures and periods. Sekiro: Shadows Die Twice, at first glance, can be considered as a game that follows the same vein of exploiting the western craze for the ninja archetype, as seen in its predecessors like the Onimusha and Tenchu series. However, it takes a bold stance against the persisting ‘self-Orientalist’ framework by reclaiming the ninja myth from marketized exoticization. Borrowing from Said’s theory of Orientalism, I would first like to analyze the existing self-Orientalism in depicting and marketing Japanese cultural icons. I would then like to highlight how this game is not an exoticized cultural artefact and further discuss the implications of such a portrayal in the contexts of representation and authenticity. I conclude that by undercutting innate stereotypes and using inherently Japanese characters, the game reappropriates the agency to depict Japanese cultural icons, from a non-Oriental, non-exoticized viewpoint. Thus, Sekiro: Shadows Die Twice becomes a stand-out in the video game industry in this respect. Bio: Geoffrey Fernandez is a PhD candidate at the Department of Humanities and Social Sciences at the Birla Institute of Technology and Science Pilani, Pilani campus. His doctoral research examines the use of culture, mythology, and folklore in video games.
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Crab-Rangoons in Kyrat: (Re)Writing South-Asian History in Far Cry 4 - Mukherjee, Souvik (Games and Culture, 2021)
Recent research has started focusing on the representation of history in videogames. Such representation is almost always of mainstream history and usually presented from a Western perspective. Set in a fictitious Himalayan kingdom in South Asia, Ubisoft’s Far Cry 4 is arguably a crucial example of how history is represented using Western and even colonial frameworks and where the narratives that do not emerge from conventional written history are almost always rendered invisible. Using the frameworks of Subaltern Studies and “border-thinking,” this essay attempts to unpack issues of Orientalism and “colonial difference”; it then engages with postcolonial digital humanities and postcolonial game studies to comment on how history is represented in videogames and how the neglected gaps and silences in the game are important in constructing the historiography in videogames. In the process, the essay engages in a debate with current notions of videogame-historiography.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Introduction to the Special Issue on Postcolonial Perspectives in Game Studies - Mukherjee, Souvik; Hammar, Emil Lundedal (Open Library of Humanities, 2018)
The treatment of colonialism in video games, barring a few notable exceptions, is marked by a Western and, specifically, late 19th-century imperialist bias. Simultaneously, in the past two decades of multifaceted research and the development of robust theoretical frameworks in the still fledgling discipline of game studies, postcolonial discourses, whether they comprise critiques of imperialism or neocolonialism, have not been prominently highlighted until very recently. A coherent effort to bring together the current research on postcolonialism in video games was also urgently required. Further, the past years has seen a rather persistent, albeit unexpected, emergence of a pro-colonial or pro-imperialist discourse in mainstream academia that even justifies the continuance of empire as an ameliorating influence on the people of the so-called developing countries, most of which had formerly been colonized by European powers.Thus, it is the aim of this issue to address this epistemic omission and counter such bias where it exists by also bridging video games research with larger discussions of postcolonialism in other humanities contexts and disciplines. The various articles in this special issue offer a range of perspectives from epistemological power to theory and praxis in critical academia, to contexts of production and practices of play, to close readings of postcolonial traces in video games. These varying approaches to the analysis of video games and their societal and historical contexts open up the debates further to a diverse set of topics ranging from board games to phone games or from mainstream high-budget console games to indie titles that question colonialism. As video games address issues relating to orientalism, subalternity, and hybridity as well as the current ambiguities in conceiving nationhood and the postcolony, the articles in this issue will also likely adumbrate further serious commentary that will develop both game studies research and current conceptions of the postcolonial.
Number: 2
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."–Provided by publisher.
OCLC: 1057550232
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Playing Subaltern: Video Games and Postcolonialism - Mukherjee, Souvik (Games and Culture, 2018)
The postcolonial has still remained on the margins of Game Studies, which has now incorporated at length, contemporary debates of race, gender, and other areas that challenge the canon. It is difficult to believe, however, that it has not defined the way in which video games are perceived; the effect, it can be argued, is subtle. For the millions of Indians playing games such as Empire: Total War or East India Company, their encounter with colonial history is direct and unavoidable, especially given the pervasiveness of postcolonial reactions in everything from academia to day-to-day conversation around them. The ways in which games construct conceptions of spatiality, political systems, ethics, and society are often deeply imbued with a notion of the colonial and therefore also with the questioning of colonialism. This article aims to examine the complexities that the postcolonial undertones in video games bring to the ways in which we read them.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Videogames and Post-Colonialism: Empire Plays Back - Mukherjee, Souvik (Palgrave MacMillan, 2017)
This book focuses on the almost entirely neglected treatment of empire and colonialism in videogames. From its inception in the nineties, Game Studies has kept away from these issues despite the early popularity of videogame franchises such as Civilization and Age of Empire. This book examines the complex ways in which some videogames construct conceptions of spatiality, political systems, ethics and society that are often deeply imbued with colonialism. Moving beyond questions pertaining to European and American gaming cultures, this book addresses issues that relate to a global audience ? including, especially, the millions who play videogames in the formerly colonised countries, seeking to make a timely intervention by creating a larger awareness of global cultural issues in videogame research. Addressing a major gap in Game Studies research, this book will connect to discourses of post-colonial theory at large and thereby, provide another entry-point for this new medium of digital communication into larger Humanities discourses.
Section: ix, 121 pages : illustrations ; 22 cm.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé